Potential natural surfactants from plant extracts for the preparation of pharmaceutical emulsions and their antimicrobial properties - Hadi, Janan Nima (Kulliyyah of Paharmacy, International Islamic University Malaysia, 2010)
Amphiphilic molecules play a key role in the stabilization of many of the colloids. It is, therefore, very important to understand the interfacial behaviour of these molecules and to select the proper ones for the proper activity. Synthetic surfactants and emulsifiers are widely used in many of our foods and pharmaceutical formulation, but, it becomes very important to replace them by natural molecules with good health records. Five medicinal plants which are Syzygium aromaticum, Entada spiralis, Trigonella foenum-graecum, Elephantopus scaber and Andrographis paniculata were selected for this study. The crude extract of the plants were prepared by maceration method. Solvents with different polarity were used for the extraction. The physical properties, in particular the surface activity of the extracts were evaluated and compared. Properties of emulsions prepared from the crude extracts were then investigated. Homogenization was carried out from 20% palm oil with 10% crude extract. The antimicrobial activities of the extracts against two Gram-positive Bacillus subtilis and Staphylococcus aureus and two Gram-negative bacteria Pseudomonas aeruginosa and Escherichia coli were investigated. Both the disc diffusion (qualitative) and tube macrodilution (quantitative) assays were employed for the determination of antimicrobial activity. The extracts of E. spiralis and S. aromaticum from ethanol-water 1:1 gave stable emulsions at least up to six months when kept at room temperature. The surface active compounds, if present among the components extracted will be adsorbed differently at the interface producing different extent of emulsion stability. All extracts were able to inhibit the growth of one or more of the bacteria. The patterns of inhibition varied with the type of plant extract, the solvent used for extraction and the organism tested. S. aureus, was the most susceptible to all plant extracts while E. coli was the most resistant microorganism. The highest antibacterial activity was observed from S. aromaticum extract with lowest minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of 0.39 mg/mL and 0.78 mg/mL, respectively against B. subtilis. It can be concluded that the extracts from S. aromaticum and E. spiralis have the potential to be used for the preparation of stable pharmaceutical emulsions by providing both emulsifying and antimicrobial actions.